Under pressure: Nanoplastics as a further stressor for sub-Antarctic pteropods already tackling ocean acidification. (January 2022) - Manno, C.; Peck, L.V.; Corsi, I.; Bergami, E.
Abstract: In the Southern Ocean (SO), plastic debris has already been found in waters and sediments. Nanoplastics (<1 μm) are expected to be as pervasive as their larger counterparts, but more harmful to biological systems, being able to enter cells and provoke toxicity. In the SO, (nano)plastic pollution occurs concomitantly with other environmental threats such as ocean acidification (OA), but the potential cumulative impact of these two challenges on SO marine ecosystems is still overlooked. Here the single and combined effects of nanoplastics and OA on the sub-Antarctic pteropod Limacina retroversa are investigated under laboratory conditions, using two surface charged polystyrene nanoparticles (PS NPs) as a proxy for nanoplastics. Sub-Antarctic pteropods are threatened by OA due to the sensitivity of their shells to changes in seawater carbonate chemistry. Short-term exposure (48 h) to PS NPs compromised the ability of pteropods to counteract OA stress, resulting in a negative effect on their survival. Our results highlights the importance of addressing plastic pollution in the context of climate change to identify realistic critical thresholds of SO pteropods. Highlights: We studied the combined impact of nanoplastics and ocean acidification on pteropods. Co-exposure to both stressors led to an increase in pteropod mortality. Plastic pollution need to be addressed in the context of global climate change.